2018
DOI: 10.33314/jnhrc.v16i3.1482
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Sacrospinous Ligament Fixation of the Vault during Repair of Pelvic Organ Prolapse

Abstract: Background: Pelvic organ prolapse includes descent of anterior/ posterior wall and apical (vault) prolapse with significant morbidity. In this study we evaluated the outcome of sacrospinous ligament fixation of vault through vaginal approach as part of the repair for massive uterovaginal (pelvic organ prolapse stage III and stage IV) and vault prolapse. Methods: This study on sacrospinous ligament fixation along with repair for pelvic organ prolapse at Kathmandu Model Hospital from November 2016 to April 2018 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The source of gluteal pain often is attributed to injury to the nerve to levator ani or pudendal nerve. 12 Small number of patients who complains of the persistent severe buttock pain may necessitate the removal of suture as reported by Dangal et al 13 in their study.…”
Section: Discussionmentioning
confidence: 84%
“…The source of gluteal pain often is attributed to injury to the nerve to levator ani or pudendal nerve. 12 Small number of patients who complains of the persistent severe buttock pain may necessitate the removal of suture as reported by Dangal et al 13 in their study.…”
Section: Discussionmentioning
confidence: 84%
“…19 Although, the type of suture material (absorbable or nonabsorbable) has an impact on the development of pain, Dangal et al, reported persistent pain after 6 months of SSLF done with absorbable sutures. 20 An earlier study reported an increase in sexual activity by 21/94 women (22.3%) after the surgery, and two recommended sexual activity. 21 Another one reported improved sexual function significantly after surgery.…”
Section: Discussionmentioning
confidence: 96%
“…However; nerve injury is unavoidable even with proper suture placement 19 . Although, the type of suture material (absorbable or nonabsorbable) has an impact on the development of pain, Dangal et al, reported persistent pain after 6 months of SSLF done with absorbable sutures 20 …”
Section: Discussionmentioning
confidence: 99%
“…But one question that needs to be raised is whether absorbable suture material does lead to lower postoperative pain, given the temporary entrapment until the suture is resolved. Although lower pain‐related complications seem likely, Dangal et al shows that absorbable sutures can also result in persistent buttock pain at 6 months after surgery 21 . However, the data are limited and the use of different suture materials for SSLF requires more evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Although lower pain-related complications seem likely, Dangal et al shows that absorbable sutures can also result in persistent buttock pain at 6 months after surgery. 21 However, the data are limited and the use of different suture materials for SSLF requires more evaluation. Nevertheless, in the case of severe direct postoperative pain, we would recommend removing the SSL sutures, regardless the type of suture material used.…”
Section: Discussionmentioning
confidence: 99%